A NEW FATIGUE MODEL OF GEAR BASED ON CONSTITUTIVE THEORY OF DAMAGE - XU HeMing; HUANG ZaiXing; QIANG Lei; XIAO Ye (Jixie qiangdu)
A new fatigue damage model is established by introducing an isotropic damage variable into the LemaitreChaboche plastic damage theory. Based on this model,a fatigue life equation is determined,that can reasonably characterize the influence of the material property,tri-axial stress ratio and stress amplitude on the fatigue life of material. The fatigue life of gears is investigated. The results show that theoretical prediction fits well with the S-N curve given by practical measuring.